Endoscopic Compared with Open Operative Treatment of Carpal Tunnel Syndrome. Issue 6 (7th June 2016) - Paryavi, Ebrahim; Zimmerman, Ryan M.; Means, Kenneth R.
Abstract : Carpal tunnel syndrome is the most common peripheral nerve compression syndrome. Treatment options include wrist-neutral bracing, corticosteroid injections, operative release of the transverse carpal ligament, and symptom-relief options. Endoscopic carpal tunnel release may give patients a faster recovery compared with traditional open release, but there are no ultimate differences in outcome among the various surgical options.